Changes in target setting for major epidemic emergency response in China before and after COVID-19 epidemic: an official documents analysis - Yushu LI; Peiwu SHI; Qunhong SHEN; Chaoyang ZHANG; Zheng CHEN; Chuan PU; Lingzhong XU; Zhi HU; Anning MA; Zhaohui GONG; Tianqiang XU; Panshi WANG; et al. (Zhongguo gonggong weisheng)
ObjectiveTo analyze changes in target setting for emergency response to major disease epidemics in China before and after the coronavirus disease 2019 (COVID-19) pandemic, summarize strengths and weaknesses in target setting, and provide a basis for improving target setting for emergency response to major disease epidemics in China. MethodsWe systematically retrieved a total of 3 864 policy documents (including plans, laws and regulations, and work programs) related to the prevention and control of major epidemics issued by government agencies of 31 provincial-level administrative divisions (PLADs) in Chinese mainland from 2000 to 2020. Relevant target content was extracted and the degree of consistency between emergency response targets for major diseases and public demand was calculated (the newly added targets are calculated on a cumulative basis from the precious year, and no value is assigned for duplicates). Paired rank sum tests were used to statistically test for differences in indicators before and after the epidemic. ResultsThe consistency between the overall goal of emergency response to major disease epidemics and public needs in China increased from 79.7% by 2019 (before COVID-19) to 91.3% in by 2020 (after COVID-19), with an increase of 14.6%, and the region-specific consistency increased from 81.2% to 93% for the eastern region and from 78.3% to 90.1% for the western region, with an increase of 14.5% and 15.1%, respectively, and a significant difference between the regions (P < 0.05). National consistency between the primary prevention goal of emergency response to major disease epidemics and public needs increased from 36.9% to 46.4%, with a significant difference between the periods before and after the COVID-19 epidemic (P < 0.05); there were no significant differences between periods in consistency between the secondary and tertiary prevention goals of emergency response to major disease epidemics and public needs at either the national or regional level. ConclusionConsistency between emergency response goals for major disease epidemics and public needs in China has increased, either at the national or regional level, especially for primary prevention goals.